Narrativa crítico-reflexiva: o impacto da pandemia pelo coronavirus no internato de medicina UFSCar - Lazarini Filho, Paulo Henrique (Universidade Federal de São Carlos, 2021)
The pandemic caused by the new SARS-CoV-2 (Severe Acute Respiratory Syndrome Coronavirus 2) was decreed by WHO in March 2020. This new global picture has led to adaptive processes in different areas of society, aiming to reduce the transmission of this virus. Among these changes was the suspension of on-site activities at federal universities. Implying stoppage of student activities and readjustment of their academic calendars. This study aims to promote a reflection on the impacts of the pandemic and its changes in daily life and expectations of this undergraduate student about to complete a bachelor's degree in medicine.
Critical relexive narrative: the pandemic COVID19 impact on internship students medicine UFSCar
Keywords: Educação de graduação em Medicina; Internato de Medicina; Pandemia COVID-19; Education; Medical; Undergraduate; Internship and residency; COVID-19; CIENCIAS DA SAUDE::MEDICINA